ANALISIS VARIANS BIAYA PRODUKSI DENGAN PERHITUNGAN BIAYA STANDAR SEBAGAI PENGENDALIAN BIAYA PRODUKSI - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2021)
TB Jelamprang is a business that is engaged in trade and industry which produces bricks and paving. In the process the raw materials into finished products are costs incurred by a company called the cost of production. This factory in producing paving and bricks have applied standard fee, but between standard costs and actual costs that have been set have never been analyzed. So that the necessary analysis of the cost of production which can be used as a benchmark in production cost control. Production cost variance analysis using Microsoft Excel 2007 can help the company perform an analysis of the cost of production for calculating the cost of production standards. The method used is quantitative and qualitative. While data collection techniques in this final report by observation, interview and documentation. Analysis of variance with a production cost calculation standard cost system using the method of analysis of the difference (The One-Way Model) made produce standard production cost reports and report actual production costs. Variance analysis calculation of production costs by using this application can save time because the sheet one with the other sheet are connected so that data already filled in automatically. Keywords: Analysis variance, Production Costs, Standard Costs